Model and Method of Calendar Planning of Logistic Processes of Enterprises of Agricultural Complex - E. S. Rodionova; T. N. Saurenko; V. G. Anisimov; E. G. Anisimov (Управленческое консультирование)
A model and method for the formation of optimal calendar plans for the organization of logistics processes for the functioning of enterprises of the agro-industrial complex have been developed. The model is based on the presentation of the procedure for the formation of an optimal calendar plan in the form of a discrete programming problem. The optimization method is based on the procedure of branches and boundaries. The proposed model and method are the basis for creating specific methods for the formation of optimal calendar plans for the organization of logistical processes of the functioning of the agro industrial complex.